The Endocrinologic Changes in Critically III Chronic Obstructive Pulmonary Disease Patients - KARAKURT, SAİT; ÇELİKEL, TURGAY HÜSEYİN (TAYLOR & FRANCIS INC, 2010)
Background: Alterations in the neuroendocrine system occur during critical illness. Chronic obstructive pulmonary disease (COPD) itself causes hormonal changes. The aim of this study was to determine neu roendocrine hormones of COPD patients with acute respiratory failure and to investigate the relationship between hormonal changes, mortality, and morbidity. Methods: We enrolled 21 patients (13 F/8 M) with COPD exacerbation requiring artificial airway support. Blood samples were collected on admission to the ICU, and on the day of hospital discharge. Eighteen healthy people were included as controls. Results: Female patients had lower luteinizing hormone (LH), follicle stimulating hormone (FSH), and free triiodothyronine (fT3), and higher prolactin (PRL) levels than controls on admission to the ICU (FSH: 70.3 vs. 29.3 mIU/mL; LH: 26.6 vs. 6.8 mIU/mL; fT3: 2.9 vs. 2.0 pg/mL; PRL: 12.4 vs. 21.3 ng/mL). Male patients had low testosterone and TSH and high PRL but only changes in TSH and PRL reached statistical significance (testosterone: 3.5 vs. 1.5 ng/mL, TSH: 1.1 vs. 0.5 uIU/mL, PRL: 9.7 vs. 14.2 ng/mL). Female patients had lower fT3 than males (fT3(female): 2.7 vs. fT3(male): 2.0 pg/mL). On follow-up, significantly elevated FSH and fT3 and decreased estradiol concentrations were documented among recovered women (FSH: 28.4 vs. 46.6 mIU/mL, fT3,: 2.0 vs. 2.6 pg/mL, E-2: 27.7 vs. 19.0 pg/mL). Patients had high C-reactive protein levels and acute physiologic and chronic health evaluation II scores. Mortality rate was 9.5% and a negative correlation between E-2 and duration of noninvasive mechanical ventilation and length of hospital stay was found in male patients. Conclusion: Men and women with acute respiratory failure in the presence of COPD develop significant changes in the neuroendocrine axis. Hormonal suppression vanishes with disease improvement.
Keywords: Exacerbation of COPD; Neuroendocrine changes; Acute respiratory failure; Artificial airway support; APACHE II score; NONTHYROIDAL ILLNESS SYNDROME; PITUITARY-TESTICULAR AXIS; TUMOR-NECROSIS-FACTOR; GONADOTROPIN-SECRETION; HYPOGONADOTROPIC HYPOGONADISM; SERUM CONCENTRATIONS; CHRONIC-BRONCHITIS; THYROID-FUNCTION; MEN; HORMONE